Xela Arias: Verso Desnudo - Expósito Rabadán, Jesús (Madrygal. Revista de Estudios Gallegos, 2005)
In this article there´s an study of Xela Arias, who died about one year ago, poetic works based upon an analisis of her poems. With just four books published between 1986 and 2003, this poet made an stand out among the Galician poets of the 80´s generation, contributing to the renoval of Galician poetry by bringing new topics and a very personal style.
Keywords: Galician poetry; 80´s poetic generation; individualism